Greek Medicine from Hippocrates to Galen Selected Papers - Jacques Jouanna, By; by Neil Allies, Translated; van der Eijk, Philip (Studies in Ancient Medicine, 2012)
This volume makes available in English translation a selection of Jacques Jouanna's papers on Greek and Roman medicine, ranging from the early beginnings of Greek medicine to late antiquity. Readership: Classicists, Ancient Historians, Historians of Medicine, Historians of Science, Historians of Philosophy, Medical Professionals.